Old dog begging for new tricks: current practices and future directions in the diagnosis of delayed antimicrobial hypersensitivity. Issue 6 (December 2016) - Konvinse, Katherine C.; Phillips, Elizabeth J.; White, Katie D.; Trubiano, Jason A.
Abstract : Purpose of review: Antimicrobials are a leading cause of severe T cell-mediated adverse drug reactions (ADRs). The purpose of this review is to address the current understanding of antimicrobial cross-reactivity and the ready availability of and evidence for in-vitro, in-vivo, and ex-vivo diagnostics for T cell-mediated ADRs. Recent findings: Recent literature has evaluated the efficacy of traditional antibiotic allergy management, including patch testing, skin prick testing, intradermal testing, and oral challenge. Although patch and intradermal testing are specific for the diagnosis of immune-mediated ADRs, they suffer from drug-specific limitations in sensitivity. The use of ex-vivo diagnostics, especially enzyme-linked immunospot, has been highlighted as a promising new approach to assigning causality. Knowledge of true rates of antimicrobial cross-reactivity aids empirical antibiotic choice in the setting of previous immune-mediated ADRs. Summary: In an era of increasing antimicrobial resistance and use of broad-spectrum antimicrobial therapy, ensuring patients are assigned the correct 'allergy label' is essential. Re-exposure to implicated antimicrobials, especially in the setting of severe adverse cutaneous reaction, is associated with significant morbidity and mortality. The process through which an antibiotic label gets assigned, acted on and maintained is still imprecise. Predicting T cell-mediated ADRs via personalized approaches, including human leukocyte antigen-typing, may pave future pathways to safer antimicrobial prescribing guidelines.